An Artificial SEI Layer Based on an Inorganic Coordination Polymer with Self-Healing Ability for Long-Lived Rechargeable Lithium-Metal Batteries - Beichel, Witali; Skrotzki, Julian; Klose, Petra; Njel, Christian; Butschke, Burkhard; Burger, Stephan; Liu, Lili; Thomann, Ralf; Thomann, Yi; Biro, Daniel; Thiele, Simon; Krossing, Ingo (Batteries & Supercaps, 2021)
Upon immersion of a lithium (Li) anode into a diluted 0.05 to 0.20 M dimethoxyethane solution of the phosphoric-acid derivative (CF3CH2O)(2)P(O)OH (HBFEP), an artificial solid-electrolyte interphase (SEI) is generated on the Li-metal surface. Hence, HBFEP reacts on the surface to the corresponding Li salt (LiBFEP), which is a Li-ion conducting inorganic coordination polymer. This film exhibits - due to the reversibly breaking ionic bonds - self-healing ability upon cycling-induced volume expansion of Li. The presence of LiBFEP as the major component in the artificial SEI is proven by ATR-IR and XPS measurements. SEM characterization of HBFEP-treated Li samples reveals porous layers on top of the Li surface with at least 3 pm thickness. Li-Li symmetrical cells with HBFEP-modified Li electrodes show a three- to almost fourfold cycle-lifetime increase at 0.1 mA cm(-2) in a demanding model electrolyte that facilitates fast battery failure (1 M LiOTf in TEGDME). Hence, the LiBFEP-enriched layer apparently acts as a Li-ion conducting protection barrier between Li and the electrolyte, enhancing the rechargeability of Li electrodes.
CRIS-Team WoS Importer:2021-12-24